A two-day bladder diary for children: Is it enough?. Issue 6 (December 2015) - Lopes, I.; Veiga, M.L.; Braga, A.A.N.M.; Brasil, C.A.; Hoffmann, A.; Barroso, U.
Summary: Introduction: A bladder diary (BD) is a simple and non-invasive method of evaluating people with lower urinary tract symptoms (LUTS). Recently, the ICCS recommended a 48-h daytime frequency and volume chart (which does not need to be recorded on 2 consecutive days) to evaluate lower urinary tract (LUT) dysfunction. However, some studies on adults have demonstrated that a minimum of 3 days is required. It is believed that, to date, there are no studies in the literature that compare a 2-day BD with a 3-day BD. The advantages of a BD over a shorter period of time are the simplicity and possible better parent compliance. Objective: The aim of this study was to evaluate if a 2-day BD is statistically and clinically comparable to a 3-day BD. Study design: A voiding diary was filled in over a 3-day period for 92 children (ages ranged from to 3–16 years, mean 7.9 ± 3.07) attending the present institution. By using the voiding diary, the following parameters were calculated: urination frequency, maximum and average volumes of urine (MVV and AVV) and fluid intake. The diary considered the 2 days as the first and second days of the 3-day diary. Results: Out of the 92 children, eight (8.7%) did not properly complete the diary. The sample predominantly comprised females ( n = 55, 59.8%). No differences were seen between 2-day and 3-day bladder diaries regarding fluid intake, maximum and average voided volume. The sensitivity, specificity, positive and negative predictive values of the 2-day bladder diary for detecting frequency were 83.4%, 91.7%, 80% and 93.2%, and for low bladder capacity they were 97.2%, 90.9%, 99% and 88%, respectively (Table ). Discussion: In a 2006 document, the ICCS recommended that a bladder diary be kept for 3 days, but in new documentation (2014) there is a reference stating that 2 days are enough. Bladder capacity is an important parameter in evaluating LUTS. Using a 2-day BD, the data showed that only a small percentage of reduced bladder capacity diagnosis would be lost. Conclusion: When using the 2-day diary, a 16% false negative rate for frequency should be expected. A 2-day bladder diary is sufficient to evaluate bladder capacity and fluid intake. Table Comparison of 2-day and 3-day voiding diaries for the number of voids and low bladder capacity. 2-day voiding diary 3-day voiding diary Higher number of voids (≥8 voids/day) Low bladder capacity (<65% of the expected bladder capacity) Yes No Total Yes No Total Yes 20 (83.4%) 5 (8.3%) 25 70 (97.2%) 1 (9.1%) 71 No 4 (16.6%) 55 (91.7%) 59 2 (2.8%) 10 (90.9%) 12 Total 24 60 84 72 11 83 *Sample of 92 children. Missing value for number of voids, eight (8.7%); for bladder capacity, nine (9.7%).